Analisis Faktor-Faktor Yang Mempengaruhi Kesempatan Kerja Di Indonesia - Silvia, Engla Desnim (journal of RESIDU, 2018)
This study aims to analyze the Influence of output, wage rate, and investment on employment opportunities in Indonesia. The type of this research is descriptive and associative research. While the type of data is documentary data, the data source is secondary data and time series data from the first quarter of 2001 until the fourth quarter of 2010. Endogenous variables in this study inflation and employment. Exogenous variables are output, interest rate, wage rate, and investment. Output, wage rates have a significant effect on employment opportunities in Indonesia. While investment has no significant effect on employment opportunities in Indonesia. Based on the results of these studies policies that can be recommended is the government needs to make policy in setting the minimum wage. In order for investment to positively affect employment opportunities in Indonesia, the company is expected to create more labor-intensive business field, so that job opportunities can increase. The government needs to provide incentives to companies that invest in businesses that absorb a lot of labor.